Quantification of Cannabinoids and their Free and Glucuronide Metabolites in Whole Blood by Disposable Pipette Extraction and Liquid Chromatography Tandem Mass Spectrometry - Scheidweiler, Karl B. (J Chromatogr A, 2016)
Identifying recent cannabis intake is confounded by prolonged cannabinoid excretion in chronic frequent cannabis users. We previously observed detection times ≤2.1 h for cannabidiol (CBD) and cannabinol (CBN) and THC-glucuronide in whole blood after smoking, suggesting their applicability for identifying recent intake. However, whole blood collection may not occur for up to 4 h during driving under the influence of drugs investigations, making a recent-use marker with a 6-8 h detection window helpful for improving whole blood cannabinoid interpretation. Other minor cannabinoids cannabigerol (CBG), Δ9-tetrahydrocannabivarin (THCV), and its metabolite 11-nor-9-carboxy-THCV (THCVCOOH) might also be useful. We developed and validated a sensitive and specific liquid chromatography-tandem mass spectrometry method for quantification of THC, its phase I and glucuronide phase II metabolites, and 5 five minor cannabinoids. Cannabinoids were extracted from 200 μL whole blood via disposable pipette extraction, separated on a C(18) column, and detected via electrospray ionization in negative mode with scheduled multiple reaction mass spectrometric monitoring. Linear ranges were 0.5-100 μg/L for THC and THCCOOH; 0.5-50 μg/L for 11-OH-THC, CBD, CBN, and THC-glucuronide; 1-50 μg/L for CBG, THCV, and THCVCOOH; and 5-500 μg/L for THCCOOH-glucuronide. Inter-day accuracy and precision at low, mid and high quality control (QC) concentrations were 95.1-113% and 2.4-8.5%, respectively (n=25). Extraction recoveries and matrix effects at low and high QC concentrations were 54.0-84.4% and −25.8-30.6%, respectively. By simultaneously monitoring multiple cannabinoids and metabolites, identification of recent cannabis administration or discrimination between licit medicinal and illicit recreational cannabis use can be improved.